On stability of generating in algebra smooth functions - Preobragensky, A. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. А. Преображенский. Об устойчивости образующих в алгебре гладких функцийA. Preobraženskis. Apie sudaromųjų stabilumą glodžių funkcijų algebroje